Pendidikan Umat dan Potensi Gerakan Sosial Online di Era Pandemi COVID-19 - Musa Maliki (Lembaga Kajian Demokrasi dan Pemberdayaan Masyarakat (LKD-PM), 2021)
Many issues are emerging during Covid-19 pandemic and one of them is mobility restriction. Some of society engagement research were still conducted in physical format with strict health protocols and some others were using hybrid methods of society engagement, combining offline and online activities. The purpose of this study is to provide an alternative way to deal with the pandemic. During pandemic, it is difficult to reach Indonesian society directly. This study conducted a series of full virtual interaction, in collaboration with the Leading Intellectual Network Community (JIB) supported mostly by Muhammadiyah young generation. The targeted audience of this society engagement were active members of JIB, its followers, and Islamic community in Indonesia at large. It focusses on actual discussion related to Covid-19 pandemic in the form of educative talk show to build public awareness. We invite credible speakers such as medical researchers, voluntary doctor on Covid-19, social scientists, and public policy advisor. This society engagement was based on Zoom platform that was broadcasted through JIB POST official website, YouTube, Facebook, and Instagram. These activities were evaluated and received feedback from WhatsApp Group JIB; expression of engagement of the audience based on subscribe, like, viewers, dan comments; and a report news on JIB POST official website. The activities presented a good result which are reaching the target of a thousand subscribers on the social media and hundreds of viewers with many positive responses from the members of JIB for every talk shows.